Terminal differentiation of bone marrow NK cells and increased circulation of TIGIT+ NK cells may be related to poor outcome in acute myeloid leukemia. Issue 4 (23rd November 2021) - Zeng, Xiangbo; Yao, Danlin; Liu, Lian; Zhang, Yikai; Lai, Jing; Zhong, Jun; Zha, Xianfeng; Lu, Yuhong; Jin, Zhenyi; Chen, Shaohua; Li, Yangqiu; Xu, Ling
Abstract: Aim: In order to further understand the feature of natural killer cell (NK) dysfunction in acute myeloid leukemia (AML), The distribution of NK cell subset the expression of the inhibitory receptors immunoglobulin and ITIM domain (TIGIT), killer cell lectin‐like receptor (KLRG1), and the expression of maturation marker CD57 in NK cell subsets and their correlation with patient outcomes were analyzed in this study. Methods: We collected peripheral blood (PB) and bone marrow (BM) samples from de novo AML (AML‐DN) patients, patients who achieved complete remission after chemotherapy (AML‐CR), and healthy individuals. An eight‐color flow cytometry panel was used to identify different NK subsets and their expression of TIGIT, CD57 and KLRG1. Results: Decreased percentage of CD56 dim CD16 + NK cells was found only in the PB of AML‐DN and AML‐CR patients but not in the BM. The expression frequency of TIGIT and KLRG1 was elevated on NK cells from the PB of AML‐DN patients, while it was recovered in AML‐CR patients. Moreover, a higher percentage of CD57 + CD56 dim CD16 + NK cells, representing a terminally differentiated NK subset with strong cytotoxic capacity but defective replication potential, was detected in the BM of AML‐DN patients and predicted sub‐optimal survival for patients. Conclusion: The results indicated that the NK cell subsets in the PB of AML patients had an exhaustion phenotype, while the BM NK cells had a terminally differentiated phenotype, which correlated with short survival for AML patients.